KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN KESADARAN MASYARAKAT UNTUK MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) DI DESA ANDONG KECAMATAN ANDONG KABUPATEN BOYOLALI - Lestari, Dewi (Transformasi, 2015)
Leadership was an individual‟s capability of leading, directing, guiding, mentoring,building, supervising, establishing good communication network, and controlling thoseexisting in its unit or facilities under his/her authority. The society‟s awareness of payingPBB was an individual‟s desire to engage in paying PBB either mentally or emotionally as anobligation, whether effort, thinking or material participation. PBB was the direct taxcollected by the central government, the revenue of which was intended to the local society‟sinterest. Recalling the importance of society‟s role in assuming the state expense, a VillageHead Leadership was required to be able to utilize the potential Land and Building taxexisting in his/her locality and to motivate his/her people to meet their obligation of payingtax. For that reason, this research aimed to find out the Village Head Leadership inimproving the society‟s awareness of Paying Land and Building Tax. Head Village was thesociety leader; a leader should recognize characteristics, situation and condition of those led.The leader should be able to create convenience in stimulating the awareness among thoseled, in this case the society‟s awareness of paying land and building. Motivation was anincentive to have someone doing anything sincerely and as well as possible. From the goodleadership, the good motivation will improve the society‟s awareness of paying Land andBuilding Tax. Considering the research conducted and followed by analyzing the dataobtained, the result was categorized into good category in the term of Village HeadLeadership in relation to the society‟s awareness of paying Land and Building Tax.Key Words: Leadership, awareness, Land and Building Tax